2021
DOI: 10.1007/s10900-020-00954-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Knowledge About the MenB Vaccine Among Parents of High School Students

Abstract: Serogroup B meningococcal disease (MenB) causes almost 60% of meningitis cases among adolescents and young adults. Yet, MenB vaccine coverage among adolescents remains below 10%. Since parents are the primary medical decision makers for adolescents, we examined MenB vaccination rates and parent attitudes about meningitis and the MenB vaccine. In 2018, in conjunction with a county-wide, school-based immunization campaign, we conducted a mixed methods study among parents of 16- to 17-year-olds. We facilitated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 40 publications
3
21
1
Order By: Relevance
“…In the current study, the main perceived benefit of vaccination was the adolescents' opportunity to resume their pre-COVID-19 routine, while the main barriers related to the vaccine's novelty and its long-term implications. While these findings are consistent with those of previous studies, emphasizing the relevance of the HBM variables for vaccination adherence in general [18,44,50], and of the perceived barriers for vaccination specifically [15,17,21,[51][52][53], the current study is novel in emphasizing the pivotal role of the perceived vaccination benefits. In addition, parents with higher levels of trust in the healthcare system were more inclined to perceive vaccination benefits as more positive, and accordingly, tended to present higher levels of adolescents' vaccination adherence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the main perceived benefit of vaccination was the adolescents' opportunity to resume their pre-COVID-19 routine, while the main barriers related to the vaccine's novelty and its long-term implications. While these findings are consistent with those of previous studies, emphasizing the relevance of the HBM variables for vaccination adherence in general [18,44,50], and of the perceived barriers for vaccination specifically [15,17,21,[51][52][53], the current study is novel in emphasizing the pivotal role of the perceived vaccination benefits. In addition, parents with higher levels of trust in the healthcare system were more inclined to perceive vaccination benefits as more positive, and accordingly, tended to present higher levels of adolescents' vaccination adherence.…”
Section: Discussionsupporting
confidence: 91%
“…Further research aimed at identifying barriers to HPV vaccination found that a low perceived risk of HPV infection, concerns regarding the vaccine's effect on sexual behavior, parental need for information, high perceived harm (from the vaccine), and low perceived vaccine effectiveness were among the leading factors presented [15]. In addition, health professionals' recommendation was found to have a strong influence on parents' decision to vaccinate their children in recommended childhood vaccinations [15][16][17][18]. As expected, adolescents living with HPV-vaccine-hesitant parents were less likely to receive the vaccine or complete the vaccine series [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that there is a lack of meningococcal disease and meningococcal vaccine knowledge among parents [ 12 , 18 , 51 , 52 , 53 , 54 ]. This lack of awareness has resulted in disparities in meningococcal vaccination rates among those in the 10- to 23-year age range.…”
Section: Resultsmentioning
confidence: 99%
“…While an incomplete understanding of vaccines or vaccine preventable diseases is certainly not unique to adolescents [21,22,79] it is important to acknowledge that adolescents may have different healthcare information needs and concerns than adults. They may also have different risk perceptions compared to adults and may be less motivated to seek preventative care [8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in this systematic review show such information should be clearly intended for and communicated directly to adolescents. While adolescents may perceive their parents to be reliable sources of vaccine information and advice, parents themselves often may not be knowledgeable about vaccines [79,84,85], underscoring the importance of continuing to provide vaccine information to parents as well as adolescents.…”
Section: Discussionmentioning
confidence: 99%